2017
DOI: 10.1021/acs.chemrev.6b00618
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Development in Solution-Processed Functional Organic Blend Films: An In Situ Viewpoint

Abstract: Solution-processed organic films are a facile route to high-speed, low cost, large-area deposition of electrically functional components (transistors, solar cells, emitters, etc.) that can enable a diversity of emerging technologies, from Industry 4.0, to the Internet of things, to point-of-use heath care and elder care. The extreme sensitivity of the functional performance of organic films to structure and the general nonequilibrium nature of solution drying result in extreme processing-performance correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
174
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(177 citation statements)
references
References 150 publications
(264 reference statements)
2
174
0
1
Order By: Relevance
“…This simple approach cannot capture subtle phenomena such as homogeneous nucleation in the solution or precipitation on a growing crystal front. Such phenomena are complex and are not entirely deciphered in today's state‐of‐the‐art. The simple precipitation model succeeded in giving a global picture of solute transport and concentration in the meniscus region, which was sufficient to drive qualitative conclusions.…”
Section: Methodsmentioning
confidence: 99%
“…This simple approach cannot capture subtle phenomena such as homogeneous nucleation in the solution or precipitation on a growing crystal front. Such phenomena are complex and are not entirely deciphered in today's state‐of‐the‐art. The simple precipitation model succeeded in giving a global picture of solute transport and concentration in the meniscus region, which was sufficient to drive qualitative conclusions.…”
Section: Methodsmentioning
confidence: 99%
“…To maintain the simplicity of the single junction structure and in the meantime broaden the absorption range of the solar cell, ternary OSCs have been developed where two donors and one acceptor or one donor and two acceptors are blended together to form the active layer. [35][36][37][38][39][40][41][42] Apparently, the morphology formed by ternary blends would be even more challenging to evaluate. [11,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] However, one main constraint that slows down the development of ternary OSC is the difficulty in controlling the morphology of ternary blends.…”
mentioning
confidence: 99%
“…Note that these highperformance laboratory devices are often produced via spin-coating, a reliable fabrication process that enables rapid prototyping and basic research. [19,20] Characterizing morphology during the film formation process can elucidate important mechanistic pathways and inform rational solution processing parameter optimization.Several recent studies have reported in situ optical and X-ray analyses of organic film growth by roll-to-roll printing, [21] blade To elucidate the details of film morphology/order evolution during spin-coating, solvent and additive effects are systematically investigated for three representative organic solar cell (OSC) active layer materials using combined in situ grazing incidence wide angle x-ray scattering (GIWAXS) and optical reflectance. [13] Traditionally, optimizing device performance relied on empirical screening of spin-casting para meters such as solvent, processing additive, and spin speed, followed by postprocessing analysis of which morphologies are produced by which coating conditions.…”
mentioning
confidence: 99%
“…Note that these highperformance laboratory devices are often produced via spin-coating, a reliable fabrication process that enables rapid prototyping and basic research. [19,20] Characterizing morphology during the film formation process can elucidate important mechanistic pathways and inform rational solution processing parameter optimization. [13] Traditionally, optimizing device performance relied on empirical screening of spin-casting para meters such as solvent, processing additive, and spin speed, followed by postprocessing analysis of which morphologies are produced by which coating conditions.…”
mentioning
confidence: 99%